Top-down and bottom-up strategies for the implementation of corporate social responsibility: A qualitative survey of an international IT services company - Matthias Gotsch; Carsten Gandenberger; Luisa Serafimov; Mathias Miemiec (Corporate Social Responsibility and Environmental Management, 2022)
Despite a large body of research on corporate social responsibility (CSR), there has been little research on the actual implementation of CSR strategies in companies. Therefore, this article examined top-down and bottom-up approaches for implementing sustainability at company level. For our survey, we chose a large IT services company, which is one of the global leaders in the Software as a Service (SaaS) business. Based on theoretical foundations, namely the Social Identity Theory and the Social Exchange Theory, six interviews were conducted with employees and managers of the company. Our results show that the company's vision and values strongly influence the employees' sustainable work activities and behavior. In addition, the employees also have options for shaping the sustainability strategy within the framework they are given. Concluding, the article shows the advantages of integrating both top-down and bottom-up approaches, and identifies options for companies implementing sustainability.
Keywords: 650; Corporate social responsibility; Implementation of sustainability strategy; Top-down/bottom-up approach; IT services